PENGARUH SILIKA TERHADAP KARAKTERISTIK FILM LATEKS KARET ALAM DALAM PENGAPLIKASIAN BLADDER COMPRESSION MOULDING - Pranata, M. Sagitra; Nugroho, G.; Indrajati, Ihda Novia; Dewi, Indiah Ratna (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The objective of this study is to investigate the production and analysis of bladders made from natural rubber latex using the dipping technique, with the aim of identifying the optimal formulation for determining their mechanical properties. The procedure was executed by a series of sequential steps, including dispersion, compaction, and vulcanization. Bladder compression molding was conducted using a range of five samples of SiO2, with varying proportions of 2, 4, 6, 8, and 10 phr. The testing was conducted in accordance with ISO 37, ISO 34-1, and ISO 188 standards. The findings indicated that the optimal formula was derived from the modification including a concentration of 2 parts per hundred of SiO2. The obtained mechanical parameters consist of a tensile strength of 17,972 MPa, an elongation at break of 924 MPa, and a tear strength of 50,478 MPa. The test parameters utilized in this study were in compliance with ISO 37, ISO 34-1, and ISO 188 standards.